Credit card market opportunity analysis of tertiary students in Singapore. - Choy, Cailin Cui Fang. (2012)
As credit spending proliferates in Singapore today, youth credit card ownership is also on the rise. The relaxation of regulations by the Monetary Authority of Singapore has allowed banks to target a younger generation with new credit card plans.